(untitled) (AYUSHDHARA, 2025)
Grihastha Ashrama is given utmost importance for continuation of human race. It is said that the family that has more progeny is always respected. In current era couple are facing difficulty to conceive naturally, this is due to the result of a combination of environmental, social, psychological, and nutritional factors. Methods: Infertility is not only a physical condition but also an emotional and a social condition, which carries very intense feelings of frustration, anger sadness, depression etc. in both the partners. The society and its culture have a major psychosocial impact on infertile couple. Incidence of infertility is increasing and artificial methods of conception like Assisted Reproductive Techniques (ART) are more on demand which are having various complications in the long run in terms of physical, mental, emotional, social wellbeing of the couple. World Health Organization (WHO) says interventions before pregnancy can increase the health and well-being of adolescents, adult women and men, and improve subsequent pregnancy and child health outcomes, highlighting the importance of pre-conceptional care. Pre-conceptional care is not a new concept, it is mentioned in Ayurveda as Garbhadana Samskara. Results & Discussion: Garbhadana Samskara is the unique technique mentioned in ancient literature which helps the couple to conceive naturally. By following the regimens told in Garbhadana samskara helps the couple to achieve a healthy progeny by healing them in physical, psychological, social and spiritual planes and ultimately attaining Shreyasi Praja. Conclusion: This article is aimed at understanding the concept of Garbhadana Samskara and its utility in current era in achieving healthy pregnancy and improved maternal and child health outcomes.